Hubungan Pemberian Asi Eksklusif Dan Pengetahuan Gizi Ibu Terhadap Status Gizi Pada Balita Usia 6 – 23 Bulan Di Puskesmas Cendrawasih Kota Makassar - Fratiwi, A. Fira; Haeruddin; Muchlis, Nurmiati (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Breast milk is the most important source of energy and nutrition for children aged 6-24 months. Breastfeeding is closely related to the nutritional status of infants. The purpose of this study was to determine the relationship between exclusive breastfeeding and maternal nutritional knowledge with the nutritional status of toddlers aged 6-23 months in the Cendrawasih Community Health Center, Mamajang District, Makassar City. This study was conducted in January and February 2023 at the Cendrawasih Community Health Center in Makassar City. The study population consisted of 52 mothers with children aged 6 to 23 months. Data collection was conducted through interviews, where questionnaires were distributed to respondents and processed using SPSS. The results of this study indicate a relationship between breastfeeding and the nutritional status of toddlers as many as 39 (97.5%), a relationship between maternal nutritional knowledge and the nutritional status of toddlers as many as 44 (97.8%) respondents, a relationship between family income and the nutritional status of toddlers as many as 21 (95.5%) respondents and a relationship between household food security and the nutritional status of toddlers as many as 22 (75.9%) respondents. From the results of statistical tests, it was found that there was a significant relationship between exclusive breastfeeding and maternal nutritional knowledge for toddlers aged 6-23 months, where p = 0.000 < α = 0.05. It can be concluded that there is a relationship between exclusive breastfeeding and nutritional knowledge, affecting toddlers' nutritional status, at the Cendrawasih Health Center in Makassar City. It is hoped that mothers and prospective mothers can increase their knowledge about nutrition and the importance of exclusive breastfeeding for babies.